REWANG: Kearifan Lokal dalam Membangun Solidaritas dan Integrasi Sosial Masyarakat di Desa Bukit Batu Kabupaten Bengkalis - Hasbullah Hasbullah (Sosial Budaya, 2012)
One local wisdom or tradition that has been maintained and continues until today in the village of Bukit Batu is a "tradition Rewang". The tradition that always accompanies the implementation activities undertaken and weddings are seen functional by the community, so that every time citizens hold weddings, the tradition is still held. In the tradition of Rewang are social values that need to be maintained, as the spirit of mutual cooperation, solidarity, social, egalitarian, and the spirit of sacrifice for others, whether to sacrifice time, matter and energy. Thus, this tradition can bring a sense of community and social solidarity, so as to reduce the tensions in society and individualistic attitudes.